2016
DOI: 10.1128/genomea.00725-16
|View full text |Cite
|
Sign up to set email alerts
|

First New World Primate Papillomavirus Identification in the Atlantic Forest, Brazil: Alouatta guariba papillomavirus 1

Abstract: We report here the complete genome sequence of the first papillomavirus detected in a New World primate, howler monkey, Alouatta guariba clamitans papillomavirus 1 (AgPV1), from the Atlantic Forest in São Paulo State, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…We identified a contig that displays 95% identity to human papillomavirus 4, which might indicate an association with virus infections in these animals, similar to what has been described from howler capuchin monkeys (Alouatta fusca) [34]. However, lesions in the oral mucosae were not observed, and these viruses may thus be part of normal microbial content, as described previously for other species [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…We identified a contig that displays 95% identity to human papillomavirus 4, which might indicate an association with virus infections in these animals, similar to what has been described from howler capuchin monkeys (Alouatta fusca) [34]. However, lesions in the oral mucosae were not observed, and these viruses may thus be part of normal microbial content, as described previously for other species [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…All genomes contained five early genes (E6, E7, E1, E2, and E4), two late genes (L2 and L1), and an upstream regulatory region (URR) between L1 and E6 genes. Phylogenetic trees based on the nucleotide sequence alignment of the concatenated four open reading frames (ORFs) (E1, E2, L2, and L1) ( Fig 1 and S1 Fig ) or individual genes, e. g., E1 or L1 ORFs ( S2 Fig , S3 Fig and S4 Fig ) support a monophyletic clade grouping SscPV1/2/3 and howler monkey Alouatta guariba PV 1 (AgPV1, KP861980) [ 24 ] within the genus Dyoomikronpapillomavirus . MmPV2 and MmPV3 cluster into the genus Alphapapillomavirus , with the closest HPVs being HPV54 (within the species Alpha-13) and HPV117 (within the species Alpha-2), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Papillomaviruses have been identified in a wide range of NHP species, including Old World monkeys and apes (e.g., macaque, chimpanzee) and New World monkeys (e.g., squirrel monkey, brown howler) [ 24 , 27 33 ]. Using a maximal likelihood algorithm and a nucleotide sequence alignment of the concatenated E1-E2-L2-L1 ORFs for 141 PV types representing each species or unique host ( S2 Table ), we found that the majority of primate PVs phylogenetically clustered into Alphapapillomavirus , Betapapillomavirus , or Gammapapillomavirus genera, corresponding predominantly to the anatomical sites where the viruses were originally isolated (e.g., mucosal or cutaneous epithelium), which was independent of the host species ( Fig 1 , S1 Fig and S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…2 ), a finding that may result from sampling bias. Previously described NP PVs were included in a single genus, Dyoomykronpapillomavirus , a sister clade of Alphapapillomavirus ( Silvestre et al. 2016 ; Chen et al 2018a,b ).…”
Section: Discussionmentioning
confidence: 99%
“…Human strains, accounting for 62 per cent ( n = 298) of these reports, are divided into five genera: Alpha- , Beta-, Gamma- , Mu- , and Nupapillomavirus . Only seventeen complete PV genomes infecting Old World Primates (OWP) are presently available, and more recently, four PV genomes infecting Neotropical Primates (NP) have been characterized ( Silvestre et al. 2016 ; Chen et al.…”
Section: Introductionmentioning
confidence: 99%